Digital quality management in construction - Marsden, Paul, 1968- (Abingdon, Oxon ; New York, NY : Routledge is an imprint of the Taylor & Francis Group, an Informa Business, 2019)
Much has been written about Building Information Modelling (BIM) driving collaboration and innovation, but how will future quality managers and engineers develop digital capabilities in augmented and video realities, with business intelligence platforms, robots, new materials, artificial intelligence, blockchains, drones, laser scanning, data trusts, 3D printing and many other types of technological advances in construction? These emerging technologies are potential game changers that require new skills and processes. Digital Quality Management in Construction is the first 'how to' book on harnessing novel disruptive technology in construction quality management. The book takes a tour of the new technologies and relates them to themanagement of quality, but also sets out a road map to build on proven lean construction techniques and embed technologically based processes to raise quality professionals' digital capabilities. With the mountain of data being generated, quality managers need to unlock its value to drive the quality of construction in the twenty-first century, and this book will help them do that and allow those working in construction Quality Management to survive and thrive, creating higher quality levels and less waste. This book is essential reading for quality managers, project managers and all professionals in the Architecture, Engineering and Construction industry (AEC). Students interested in new and disruptive technologies will also learn a great deal from reading this book, written by a professional quality manager with nearly thirty years' experience in both the public and private sectors.
Ancient world construction quality (Paleolithic-500CE) -- Middle ages and discovery age construction quality (500CE-1800CE) -- Post-Industrial Age construction quality & lean (1800CE-2000CE) -- Modern quality management -- Quality information model -- Data & information management -- Business intelligence & data trusts -- Quality management culture & governance -- Digital capabilities -- Web based process management -- Drones -- Construction plant -- autonomous vehicles & telemetry -- Robotics, lasers & 3D printing -- Augmented reality (AR), mixed reality (MR) & virtual reality (VR) -- Wearable & voice controlled technology -- Blockchains -- Artificial Intelligence (AI) -- Advanced materials -- Future technology -- Roadmap to digital quality management.
OCLC-licensed vendor bibliographic record.
Keywords: Building -- Quality control -- Data processing; Building -- Quality control -- History; TECHNOLOGY & ENGINEERING / Civil / General; ARCHITECTURE / Professional Practice; ARCHITECTURE / Project Management